The Relationship of Self-Presentation, Psychological Needs, and Exercise Dependence in College Students With Overweight - Liu, YiWen; Liu, Hao; Liu, ZhongQiang (Frontiers in Psychology, 2021)
To explore the effect of self-presentation and psychological needs on exercise dependence, and to provide an essential reference for preventing and inhibiting the production of exercise dependence in overweight college students. Methods: The freshmen in two comprehensive universities accepted physical fitness tests filled out the scales of self-presentation, psychological needs, and exercise dependence after obtaining their consent. A sample of 747 overweight college students with regular exercise was screened using the formula of Fox sports participation and the standard of overweight in Chinese adults. Multiple regression, exploratory factor, and confirmatory factor analyses were used to analyze the related data. Results: 1) Male and female overweight college students showed that individuals with higher physical attractiveness were more likely to suffer from detoxification of emotion, physiology, and vitality, and higher ability presentation were more likely to appear in physiological abstinence.2) The self-presentation of male and female overweight students has a significant positive influence on psychological needs and exercise dependence. In contrast, psychological needs have a significant negative influence on exercise dependence (beta = -0.21**, -0.26**). 3) The psychological needs of male and female overweight students were established as the intermediary role of self-presentation and exercise dependence. The intermediary effect of female psychological needs was higher than that of males (18.5% vs. 15.5%). The "ability display" of male and female students can affect "emotional distress" by "autonomy" and "competence." The sense of relationship partly mediated the "attraction" of male and female students. And females, on the one hand, rely on "weight control" by "competence" to produce some mediating effects on "physiological distress." At the same time, the "ability display" by "competence" has a full intermediary effect on "physiological distress." Conclusion: In the self-presentation structure of the overweight college students, the higher scores in "attractive," "weight control," and "ability display," the higher psychological needs and exercise dependence; the higher autonomy, competence, and relationship, the less the emotional, physiological and dynamic distress.